CONCORDÂNCIA NOMINAL EM GUARAPUAVA, PARANÁ - FONSECA, TATIANE DA LUZ WALCZAK DA (2016)
The current study has as objective to analyze the use of the nominal agreement rule for plural numbers in the municipality of Guarapuava, Paraná. At first, we briefly discuss the Variationist Sociolinguistic theory, in which this research is based, and then it is presented some of the works of its precursor, William Labov ([1972] 2008). In the following, we approach our study subject, the nominal agreement and briefly present some previous studies on the subject, being them: Braga & Scherre (1976); Braga (1977); Poplack (1980); Scherre (1988; 1998); and Fernandes (1996). For the analysis of the nominal agreement in Guarapuava, the linguistic variables initially considered were: phonic salience, tonicity, position of the element in SN, grammatical class of the element and previous marks. Afterwards, it was performed another round combining the variables allying the variables phonic salience and tonicity, as wells as the variables position of the element in SN and grammatical class. The social variables considered were: gender, age range and education. The analyzed data belong to the Guarapuava database (VARLINGUA), being composed by 24 interviews, distributed by gender (female and male), age range (25 to 45 years old and 50 years or more) and education (primary, elementary and high school), transcribed and encoded. For the data analysis, we used the statistical software GoldVarbX. Linguistic factors that favored the presence of CN were: determinants (articles, possessives, indefinite and quantifiers), prefixed to the word in the 2nd and 1st position, the absence of a preceding element, the absence of morphological mark in the previous element, the double plural, the items ending in -l and the items ending in -s. The social factors that favored the presence of CN were: the speakers at studied only to the elementary school and the female speakers. With this study, we hope to contribute for the description of the nominal agreement and for the linguistic variation studies in the South of Brazil.